Failure investigation of packaged SiC-diodes after thermal storage in extreme operating condition. (January 2018) - Latry, Olivier; Dherbecourt, Pascal; Denis, Patrick; Cuvilly, Fabien; Kadi, Moncef
Abstract: Ageing tests through thermal storage at high temperature (240 °C) are carried out on commercial Schottky diodes in TO220 package, in "derating mode" operational conditions. The analysis revealed a failure mechanism, resulting into vaporization of the moisture present in significant quantity in the resin/sole interface. As a consequence, a degradation of the resin, freeing up space, caused the solder to spread under the chip. The X-ray analyses, acoustic microscopy SAM, optical and electron microscopy are used to describe the failure mechanism. We note that the resin package has undergone a strong degradation. Investigations show that this phenomenon is fully responsible for the degradation process taking place in derating mode use. Most components behave similarly with respect to the ageing; however, an atypical and unusual result is revealed for one component after the ageing process. Thus, the specific case is presented as a potentially decisive case for the validation of a failure analysis, so that technical solution can be formed. Highlights: A complete failure analysis of power SiC diode is proposed after ageing. The thermal storage leads to the solder joint degradation. Electrical characterizations are performed as a failure indicator. A complete structural analysis confirms the electrical measurement degradation after ageing process.